Tanggung Jawab Pers dan Regulasi Hukum Berita Bohong dalam Pemberitaan - Wiwit Tasya Fitrianna; Fitra Akbar; Dania Pramesywari; Taun Taun (Lembaga Pengembangan Kinerja Dosen, 2025)
The dissemination of information that cannot be proven true or what is often called fake news is very vulnerable today. In reporting, the press has a responsibility in the event of an objection to a news report. Based on the Press Law, the press is obliged to serve the right of reply and the right of correction to public complaints about press coverage. Regarding fake news in Indonesia, the regulations are contained in the Criminal Code, ITE Law, Broadcasting Law and other laws. This research aims to find out the regulations that become the legal umbrella for victims of fake news perpetrated by the press and the extent to which the press is responsible for fake news in the news. The research method used is a literature study using primary, secondary and tertiary legal materials.